Method for producing high nickel positive electrode active material
By directly leaching and coprecipitating metal components from raw materials, the manufacturing process for high-nickel positive electrode active materials is streamlined, reducing time and cost while producing a high-capacity, stable electrode material for lithium secondary batteries.
Patent Information
- Application Number
- JP2023522889
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-10-13
- Filing Date
- 2021-10-14
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2041-10-14
AI Technical Summary
The existing manufacturing processes for high-nickel positive electrode active materials are time-consuming and costly due to the need for additional smelting and liquefaction processes, particularly when producing high nickel content materials.
A method involving direct leaching of metal components from raw materials containing nickel and cobalt, followed by the use of a chelating agent and hydroxide precipitant to coprecipitate a positive electrode active material precursor, eliminating the need for reducing and separating intermediates, and incorporating a liquid phase intermediate containing nickel, cobalt, and manganese sulfates directly into the production process.
This method simplifies the smelting and liquefaction processes, reducing time and cost while maintaining high nickel content, resulting in a structurally stable and high-capacity positive electrode active material for lithium secondary batteries.
Smart Images

Figure 0007607760000002 
Figure 0007607760000003 
Figure 0007607760000004
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2020-0132451 filed on October 14, 2020, and Korean Patent Application No. 10-2021-0136143 filed on October 13, 2021, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.
[0002] The present invention relates to a method for producing a high-nickel positive electrode active material having a nickel content of 60 at% or more, more particularly, to a method for producing a high-nickel positive electrode active material, which can reduce time and cost by leaching metal components from a raw material containing nickel and cobalt, and then directly inputting the leached metal components into a process for producing a positive electrode active material precursor, thereby simplifying the smelting and liquefaction processes. [Background technology]
[0003] In recent years, as mobile devices and power tools have become more common and the demand for environmentally friendly electric vehicles has increased, the requirements for the energy sources that drive them have gradually increased. In particular, there is a demand for the development of positive electrode active materials that have high energy density, stable operation under high voltage, and long life characteristics.
[0004] Lithium transition metal composite oxides are used as the positive electrode active material for lithium secondary batteries, and among them, the lithium cobalt composite metal oxide LiCoO2, which has a high working voltage and excellent capacity characteristics, is mainly used. However, LiCoO2 has very poor thermal properties due to the instability of its crystal structure caused by delithiation, and is expensive, so there is a limit to its mass use as a power source in fields such as electric vehicles.
[0005] Materials that have been developed to replace LiCoO2 include lithium manganese composite metal oxides (LiMnO2 or LiMn2O4, etc.), lithium iron phosphate compounds (LiFePO4, etc.), and lithium nickel composite metal oxides (LiNiO2, etc.). However, LiNiO2 has poorer thermal stability than LiCoO2, and if an internal short circuit occurs due to external pressure while the battery is charged, the positive electrode active material itself will decompose, resulting in the battery exploding or catching fire.
[0006] As a result, nickel-cobalt-manganese-based lithium composite transition metal oxides (hereinafter simply referred to as "NCM-based lithium oxides") were developed in which part of the Ni was replaced with Mn and Co as a way to improve the low thermal stability of LiNiO2 while maintaining the excellent reversible capacity. However, the capacity characteristics of the NCM-based lithium oxides developed up to now have been insufficient, limiting their application.
[0007] In order to improve these problems, research has been conducted in recent years to increase the Ni content in NCM-based lithium oxides to improve the capacity characteristics of the positive electrode active material. In recent years, high-nickel positive electrode active materials that contain 60 atm% or more of Ni among the total transition metals have been developed.
[0008] The nickel metal used in the NCM-based positive electrode active material can be obtained by reducing nickel sulfate, an intermediate product of the iron smelting process, after an additional smelting process. Meanwhile, to produce a positive electrode active material precursor, nickel metal must be produced again from nickel sulfate, or an intermediate powder (NiSiO4·6H2O) must be dissolved and used for ease of transportation and storage.
[0009] That is, currently, in order to prepare a positive electrode active material precursor, nickel metal must be obtained from nickel oxide ore ore ore and then converted to nickel sulfate, which requires excessive time and cost. In particular, in the case of a high-nickel positive electrode active material, a high content of nickel is required, which significantly increases the time and cost.
[0010] Therefore, there is a demand for the development of a new technology that can further simplify the manufacturing process of high-nickel positive electrode active materials. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Korean Patent Publication No. 10-2016-0063982 (Published June 7, 2016) Summary of the Invention [Problem to be solved by the invention]
[0012] The present invention aims to improve the manufacturing process of high-nickel positive electrode active material, and aims to provide a manufacturing method of high-nickel positive electrode active material that can reduce time and cost by leaching metal components from raw materials containing nickel and cobalt, and then directly inputting the leached metal components into a manufacturing process of a positive electrode active material precursor without reducing and separating the metal components, thereby simplifying the smelting and liquefaction processes.
[0013] The present invention also provides a method for producing a high-nickel positive electrode active material, which can easily produce a positive electrode active material containing a high nickel content of 60 atm% or more by directly adding a liquid phase intermediate containing nickel sulfate, cobalt sulfate and manganese sulfate obtained from a raw material containing nickel and cobalt to a production process of a positive electrode active material precursor, and further adding a certain amount of nickel sulfate, cobalt sulfate or manganese sulfate. [Means for solving the problem]
[0014] In order to achieve the above object, the present invention provides a method for producing a high-nickel positive electrode active material, the method including the steps of: preparing a raw material containing nickel and cobalt; leaching metal components in the raw material using an acid and removing impurities to separate a liquid phase intermediate; and adding a chelating agent and a hydroxide precipitant to the liquid phase intermediate to coprecipitate a positive electrode active material precursor.
[0015] The present invention also provides a method for producing a high-nickel positive electrode active material, in which the raw material containing nickel and cobalt is nickel oxide ore or nickel sulfide ore.
[0016] The present invention also provides a method for producing a high-nickel positive electrode active material, wherein the liquid phase intermediate contains nickel sulfate, cobalt sulfate, and manganese sulfate.
[0017] The present invention also provides a method for producing a high-nickel positive electrode active material using a liquid phase intermediate containing 35% by weight to 65% by weight of nickel and 1.5% by weight to 7% by weight of cobalt.
[0018] The present invention also provides a method for producing a high-nickel positive electrode active material, in which the cobalt / nickel content ratio in the liquid phase intermediate is 0.03 to 0.13.
[0019] The present invention also provides a method for producing a high-nickel positive electrode active material, comprising the step of further adding at least one selected from the group consisting of nickel sulfate, cobalt sulfate, and manganese sulfate after the step of separating the liquid phase intermediate.
[0020] In addition, the present invention provides a method for preparing a high-nickel positive active material, further comprising the step of mixing the positive active material precursor with a lithium source material, and calcining the mixture to prepare a lithium composite metal oxide.
[0021] The present invention also provides a method for producing a high-nickel positive electrode active material, wherein the lithium composite metal oxide is represented by the following Chemical Formula 1:
[0022] Li a Ni b Co c Mn d MeO2
[0023] In the formula 1, M is at least one selected from the group consisting of W, Cu, Fe, Ba, V, Cr, Ti, Zr, Zn, In, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; 0.9≦a≦1.5, 0.8≦b<1.0, 0 <c<0.2、0<d<0.2、0≦e≦0.02である。
[0024] The present invention also provides a method for producing a high-nickel positive active material, wherein the step of leaching metal components in the raw material using an acid is performed using a High Pressure Acid Leaching (HPAL) method.
[0025] The present invention also provides a method for producing a high-nickel positive electrode active material, wherein the step of leaching the metal components in the raw material using the acid comprises leaching in sulfuric acid under high temperature and pressure using an autoclave.
[0026] The present invention also provides a method for producing a high-nickel positive electrode active material, in which the content of nickel relative to the total amount of metals excluding lithium in the positive electrode active material is 60 atm % or more.
[0027] The present invention also provides a method for producing a high-nickel positive electrode active material that does not include a step of reducing the liquid phase intermediate. Effect of the Invention
[0028] According to the method for producing a high-nickel positive electrode active material of the present invention, after leaching metal components from a raw material containing nickel and cobalt, the leached metal components are not reduced and separated, but are directly input into a process for producing a positive electrode active material precursor, thereby simplifying the smelting and liquefaction processes, and thereby reducing the time and cost required for producing a positive electrode active material. [Brief description of the drawings]
[0029] [Figure 1] FIG. 2 is a schematic diagram showing a process for producing a high-nickel positive electrode active material according to the present invention. [Diagram 2]FIG. 2 is a diagram showing a process for producing a high-nickel positive electrode active material according to the present invention, further comprising a step of adding nickel sulfate, cobalt sulfate, or manganese sulfate. [Diagram 3] FIG. 1 is a schematic diagram showing a comparison between the manufacturing process of a high-nickel positive electrode active material according to the present invention and the prior art. [Figure 4] FIG. 2 is a schematic diagram showing a comparison between a conventional process and a process for producing a positive electrode active material according to the present invention using nickel oxide ore. [Diagram 5] FIG. 2 is a schematic diagram showing a comparison between a conventional process and a process for producing a positive electrode active material according to the present invention using nickel sulfide ore. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] The embodiments provided by the present invention can all be achieved by the following description. It should be understood that the following description describes preferred embodiments of the present invention, and that the present invention is not necessarily limited thereto.
[0031] The present invention provides a method for producing a high-nickel positive electrode active material, the method including the steps of: preparing a raw material containing nickel and cobalt; leaching metal components in the raw material using an acid and removing impurities to separate a liquid phase intermediate; and adding a chelating agent and a hydroxide precipitant to the liquid phase intermediate to coprecipitate a positive electrode active material precursor.
[0032] In one embodiment of the present invention, the raw material containing nickel and cobalt may be nickel oxide ore or nickel sulfide ore. In the method for producing a high-nickel positive electrode active material of the present invention, a method for producing a high-nickel positive electrode active material using nickel oxide ore is specifically shown in FIG. 4, and a method for producing a high-nickel positive electrode active material using nickel sulfide ore is specifically shown in FIG. 5, but is not limited thereto.
[0033] Nickel ore, which is a raw material containing nickel and cobalt, is largely divided into nickel sulfide ore and nickel oxide ore, laterite ore. Nickel sulfide ore can easily improve the nickel grade through physical beneficiation processes such as stage-grinding, gravity separation, and flotation, and was used as a raw material to produce 60% of the world's nickel production in 2011. However, economically minable nickel sulfide ore has been depleted due to long-term resource development, and interest in laterite ore, which accounts for more than 70% of the total nickel reserves, is increasing. Nickel oxide ore, laterite ore, is an oxide ore formed by weathering rocks due to high temperatures and abundant rainfall in equatorial regions. It is divided into wet laterite, which exists in tropical regions, and dry laterite, which is distributed in Australia, and the strata structure and ore content vary depending on the region. Such laterite ores have a depth of about 10 to 20 m from the surface of the earth, and as the depth increases, the composition (mineral phase) and physical properties change. Limonite is FeO(OH) n It is a component of H2O and can be in the form of lumps, earth, powder or fibers.
[0034] Saprolite refers to chemically weathered rocks, and most of them have a soft and brittle structure. The saprolite layer is divided into upper saprolite and lower saprolite, and the upper one is generally yellow, ochre, orange or yellowish brown, and its structure and texture are almost completely maintained. The lower one is generally greenish, but has harder mineral properties than the upper saprolite. Garnierite, the main mineral of saprolite ore, is formed by the weathering of serpentine and ultra-ferric rocks. Garnierite has a high nickel content and is not a single mineral, but contains talc, lizardite, sepiolite, etc. Among nickel oxide ores, the ore currently used industrially is saprolite, which has a relatively high nickel content, and saprolite generally contains 1.5 to 2.5% nickel and 10 to 20% iron. In general, laterite ore can be present in a layered configuration of limonite, which has a relatively low magnesium content and a high iron content, and saprolite, which has a relatively high magnesium content and a low iron content, in which nickel and cobalt are in the form of oxides. Specifically, limonite is composed of 50-70% Fe -2 In one embodiment, saprolite may be a mineral component containing 7-27% Fe2O3 and up to 10% MgO.
[0035] In one embodiment of the present invention, the step of leaching metal components from the raw material containing nickel and cobalt can be performed by dissolving in acid in an autoclave under high temperature and pressure to recover nickel, cobalt, etc. (HPAL method (High Pressure Acid Leaching)). Here, nickel oxide ores such as limonite and saprolite have passive properties in an oxide state, so they have high resistance to acid and have a slow reaction to dissolution in acid. Therefore, nickel, cobalt, etc. contained in the raw material can be leached by the HPAL method.
[0036] Specifically, the leaching of nickel, cobalt, etc. by the HPAL method is preferably carried out in an autoclave at a temperature of 230°C to 270°C and a pressure of 40 to 50 bar. The acid used is preferably concentrated sulfuric acid. The reaction time is preferably about 30 minutes to 120 minutes, and the leaching rate by the HPAL method exceeds 90%. In addition, after leaching with sulfuric acid in the HPAL method, the residue is separated and the residual acid in the leachate is neutralized, and then nickel and cobalt can be separated and recovered through various processes.
[0037] In one embodiment of the present invention, the removal of impurities from the leaching solution can be repeatedly carried out by a conventional method in the technical field of the present invention, such as partial crystallization, fractional distillation, solvent extraction, etc., and preferably, solvent extraction can be used. Considering such a solvent extraction method, an alkali metal compound or an alkaline earth metal compound, or an alkali compound such as NaOH, NH3, or NH4OH can be used as a neutralizing agent to adjust the pH during solvent extraction.
[0038] In addition, the solvent extraction method can use DEPA (di-2-ethylhexyl phosphoric acid) or BTMPA (bis(2,4,4-trimethylpentyl)phosphonic acid). Specifically, nickel can be extracted using DEPA (di-2-ethylhexyl phosphoric acid) at pH 6, cobalt can be extracted using BTMPA (bis(2,4,4-trimethylpentyl)phosphonic acid) at pH 5, and manganese can be extracted using DEPA (di-2-ethylhexyl phosphoric acid) at pH 2. Since the present invention is produced using raw ore, the yield of the final product can be improved by varying the pH as described above in consideration of the content of metals contained in the raw ore.
[0039] In one embodiment of the present invention, the liquid phase intermediate may include nickel sulfate, cobalt sulfate, and manganese sulfate. The nickel content in the liquid phase intermediate may be 35% by weight to 65% by weight based on the total metal, and the cobalt content may be 1.5% by weight to 7% by weight. In addition, the cobalt / nickel content ratio in the liquid phase intermediate may be 0.03 to 0.13. When the nickel and cobalt contents satisfy the above ranges, it is more advantageous to manufacture the high-nickel positive electrode active material according to the present invention.
[0040] In one embodiment of the present invention, the step of separating the liquid phase intermediate may further include a step of adding at least one selected from the group consisting of nickel sulfate, cobalt sulfate, and manganese sulfate. By including the step, the concentration can be adjusted according to the composition so as to be suitable for producing the high nickel positive electrode active material precursor according to the present invention.
[0041] In one embodiment of the present invention, a chelating agent and a hydroxide precipitant are added to the liquid phase intermediate to perform a co-precipitation reaction to prepare a positive electrode active material precursor.
[0042] The chelating agent may be a complexing agent containing an ammonium cation, such as, but not limited to, NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, NH4CO3, or a combination thereof. Meanwhile, the chelating agent may be used in the form of an aqueous solution, and in this case, the solvent may be water or a mixture of water and an organic solvent (e.g., alcohol) that is uniformly miscible with water.
[0043] The hydroxide precipitant may be a hydroxide of an alkali metal or an alkaline earth metal, such as NaOH, KOH, or Ca(OH)2, a hydrate thereof, or a combination thereof. The hydroxide precipitant may also be used in the form of an aqueous solution, and in this case, the solvent may be water or a mixture of water and an organic solvent (e.g., alcohol) that is uniformly miscible with water.
[0044] The hydroxide precipitant is added to adjust the pH of the reaction solution, and can be added in an amount that results in a metal solution having a pH of 11-13.
[0045] Meanwhile, the coprecipitation reaction can be carried out at a temperature of 40°C to 70°C under an inert atmosphere such as nitrogen or argon.
[0046] Through the above process, nickel-cobalt-manganese hydroxide particles are produced and precipitated in the reaction solution. The process includes a step of adding at least one selected from the group consisting of nickel sulfate, cobalt sulfate, and manganese sulfate, and by adjusting the concentrations of nickel sulfate, cobalt sulfate, and manganese sulfate, a precursor having nickel (Ni) of 60 at% or more relative to the total amount of metals excluding lithium can be produced. The precipitated nickel-cobalt-manganese hydroxide particles are separated and dried by a conventional method to obtain a positive electrode active material precursor.
[0047] In one embodiment of the present invention, the method for preparing the high nickel positive active material may further include a step of preparing a lithium composite metal oxide by mixing the positive active material precursor with a lithium source material and calcining the mixture. Specifically, the positive active material precursor and the lithium source material may be mixed and subjected to a primary plasticization under an oxidizing atmosphere to form a plastic material. The lithium source material may be a lithium-containing sulfate, nitrate, acetate, carbonate, oxalate, citrate, halide, hydroxide, or oxyhydroxide, and is not particularly limited as long as it is soluble in water. Specifically, the lithium source material may be Li2CO3, LiNO3, LiNO2, LiOH, LiOH·H2O, LiH, LiF, LiCl, LiBr, LiI, CH3COOLi, Li2O, Li2SO4, CH3COOLi, or Li3C6H5O7, and any one or a mixture of two or more of these may be used.
[0048] The first plasticization is performed in an oxidizing atmosphere, and the oxidizing atmosphere may mean that the firing is performed while supplying oxygen. 2 / min~600m 2 / min, and more preferably 200m 2 / min~400m 2 / min.
[0049] The firing temperature for the primary plasticization may be 400° C. to 700° C., more preferably 450° C. to 650° C., and further preferably 500° C. to 600° C. By performing the primary plasticization within the firing temperature range, lithium and the precursor react with each other to more quickly generate a plastic material having a layered structure and a spinel-like structure, and the amount of oxygen consumed may be reduced.
[0050] The primary plasticization can be performed for 3 to 7 hours after the target firing temperature is reached, and more preferably for 4 to 6 hours. By performing the primary plasticization within the firing time range, the structural stability of the final positive electrode active material can be effectively improved, the moisture content can be reduced, and a uniform reaction can be induced to produce a positive electrode active material with uniform performance with less scattering, and only the amount of oxygen required for performance improvement can be consumed, thereby improving production efficiency.
[0051] In this way, the plastic material formed through the first plasticization may have a structure including a layered structure and a spinel-like structure. Since the plastic material has a structure including a layered structure and a spinel-like structure, there is sufficient oxygen in the structure, so there is no need to maintain an oxidizing atmosphere thereafter. Therefore, in the subsequent second main sintering, the oxygen supply is stopped to reduce oxygen consumption, and the internal temperature drop of the sintering furnace due to the oxygen input can be prevented, so that a positive electrode active material with excellent crystallinity and uniformity can be produced even when sintered at the same sintering temperature.
[0052] Next, the plastic material is subjected to a second main sintering in an air atmosphere to form a lithium transition metal oxide.
[0053] As described above, the second main firing can be performed in an air atmosphere without maintaining the oxidizing atmosphere in the first plasticity, i.e., after the supply of oxygen in the first plasticity is stopped. Since the plastic material formed in the first plasticity has a layered structure and a spinel-like structure, it is not necessary to continuously supply oxygen in the second main firing. Rather, it is possible to manufacture a lithium transition metal oxide cathode active material having excellent crystallinity and improved structural stability by preventing a temperature drop caused by oxygen input and promoting a uniform reaction between the cathode active material precursor and the lithium raw material source. In addition, since oxygen is supplied only in the first plasticity, the oxygen consumption can be significantly reduced compared to the previous manufacturing process in which the entire firing process was performed in an oxidizing atmosphere, thereby reducing manufacturing costs.
[0054] The firing temperature of the secondary main firing may be 700° C. to 1,000° C., more preferably 725° C. to 900° C., and further preferably 750° C. to 800° C. By performing the secondary main firing within the above firing temperature range, it may be possible to synthesize a positive electrode active material that is structurally less prone to cation mixing (cation disorder) and is electrochemically excellent.
[0055] The secondary main firing can be carried out for 4 to 15 hours after the target firing temperature is reached, and more preferably for 5 to 10 hours.
[0056] The lithium transition metal oxide thus formed may be, for example, represented by the following Chemical Formula 1:
[0057] [Chemical formula 1] Li a Ni b Co c Mn d MeO2
[0058] In Chemical Formula 1, M is one or more selected from the group consisting of W, Cu, Fe, Ba, V, Cr, Ti, Zr, Zn, In, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; 0.9 ≦ a ≦ 1.5, 0.7 ≦ b < 1.0, 0 < c < 0.2, 0 < d < 0.2, and 0 ≦ e ≦ 0.02.
[0059] In the lithium transition metal oxide of Chemical Formula 1, Li may be contained in an amount corresponding to a, that is, 0.9 ≦ p ≦ 1.5. If a is less than 0.9, the capacity may decrease. If it exceeds 1.5, the strength of the fired positive electrode active material becomes high and it is difficult to pulverize, and there may be an increase in the amount of gas generation due to an increase in Li by-products. Considering the effect of improving the capacity characteristics of the positive electrode active material by controlling the Li content and the sinterability balance during the production of the active material, the Li can more preferably be contained in an amount of 1.0 ≦ a ≦ 1.1.
[0060] Also, in the lithium transition metal oxide of Chemical Formula 1, Ni may be contained in an amount corresponding to b, for example, 0.7 ≦ b < 1.0. When the content of Ni in the lithium transition metal oxide of Chemical Formula 1 becomes a composition of 0.7 or more, a sufficient amount of Ni for contributing to charge and discharge is ensured, and further high capacity can be achieved.
[0061] In the lithium transition metal oxide of Chemical Formula 1, Co may be contained in an amount corresponding to c, that is, 0 < c < 0.2. If the content of Co in the lithium transition metal oxide of Chemical Formula 1 is 0.2 or more, there is a risk of increased cost.
[0062] In the lithium transition metal oxide of Chemical Formula 1, Mn may be contained in an amount corresponding to d, that is, 0 < d < 0.2. Mn can improve the stability of the positive electrode active material and, as a result, improve the stability of the battery.
[0063] In the lithium transition metal oxide of Formula 1, M may be a doping element contained in the crystal structure of the lithium transition metal oxide, and M may be contained in a content corresponding to e, that is, 0≦e≦0.02.
[0064] In one embodiment of the present invention, the positive electrode active material may have a nickel content of 60 at% or more, preferably 75 at% or more, and more preferably 80 at% based on the total amount of metals excluding lithium. By satisfying the nickel content, the positive electrode active material can realize a secondary battery that is not only structurally stable but also has excellent capacity characteristics and a small resistance increase rate during repeated charging.
[0065] In one embodiment of the present invention, the method for producing a high-nickel positive active material may not include a process of reducing and precipitating the liquid phase intermediate. That is, the liquid phase intermediate may be reduced and precipitated to produce a positive active material without separating nickel, cobalt, or manganese into pure metals. This eliminates the need for a process of refining nickel and cobalt, which are difficult to separate, in the final step, and simplifies the smelting and liquefaction processes, thereby reducing the time and cost required to produce a high-nickel positive active material.
[0066] In addition, when the high nickel lithium transition metal oxide positive electrode active material produced by the production method of the present invention is used, the initial resistance of the lithium secondary battery can be reduced, the high temperature life characteristics can be improved, and an increase in resistance can be suppressed.
[0067] Positive electrode and secondary battery The high-nickel positive electrode active material produced by the production method of the present invention can be usefully used in producing positive electrodes for secondary batteries.
[0068] Specifically, the positive electrode for a secondary battery according to the present invention includes a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, and the positive electrode active material layer includes the positive electrode active material according to the present invention.
[0069] The positive electrode may be manufactured by a conventional method for manufacturing a positive electrode, except for using the positive electrode active material according to the present invention. For example, the positive electrode may be manufactured by dissolving or dispersing the components constituting the positive electrode active material layer, i.e., the positive electrode active material, and a conductive material and / or a binder, in a solvent to manufacture a positive electrode mixture, applying the positive electrode mixture to at least one surface of a positive electrode current collector, and then drying and rolling the mixture, or by casting the positive electrode mixture on a separate support, peeling the mixture from the support, and laminating the resulting film on the positive electrode current collector.
[0070] In this case, the positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector may usually have a thickness of 3 μm to 500 μm, and fine irregularities can be formed on the surface of the current collector to increase the adhesive force of the positive electrode active material. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0071] A positive electrode active material layer containing the positive electrode active material according to the present invention and optionally further containing at least one of a conductive material and a binder is located on at least one surface of the current collector.
[0072] The positive electrode active material includes the positive electrode active material according to the present invention, i.e., the lithium composite metal oxide represented by Chemical Formula 1. The specific content of the positive electrode active material according to the present invention is the same as that described above, and therefore a detailed description thereof will be omitted.
[0073] The positive electrode active material may be contained in a content of 80 to 99 wt %, more specifically 85 to 98 wt %, based on the total weight of the positive electrode active material layer. When the content is within the above range, excellent capacity characteristics can be exhibited.
[0074] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one or more of these can be used alone or in combination. The conductive material can be contained in an amount of 1% by weight to 30% by weight based on the total weight of the positive electrode active material layer.
[0075] The binder also plays a role in improving the adhesion between particles of the positive electrode active material and the adhesive strength between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these can be used alone or in combination. The binder can be included in an amount of 1 wt% to 30 wt% based on the total weight of the positive electrode active material layer.
[0076] Meanwhile, the solvent used in the preparation of the positive electrode composite may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, water, etc., which may be used alone or in combination. The amount of the solvent used may be appropriately adjusted in consideration of the coating thickness, production yield, viscosity, etc. of the slurry.
[0077] Next, the secondary battery according to the present invention will be described.
[0078] The secondary battery according to the present invention includes a positive electrode, a negative electrode facing the positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode is the positive electrode according to the present invention described above.
[0079] Meanwhile, the secondary battery may further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.
[0080] In the secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector.
[0081] The negative electrode may be manufactured by a conventional method for manufacturing a negative electrode that is generally known in the art. For example, the negative electrode may be manufactured by dissolving or dispersing components constituting the negative electrode active material layer, i.e., the negative electrode active material, a conductive material, and / or a binder, in a solvent to manufacture a negative electrode mixture, applying the negative electrode mixture to at least one surface of a negative electrode current collector, and then drying and rolling the mixture, or by casting the negative electrode mixture on a separate support, peeling it off from the support, and laminating the resulting film on the negative electrode current collector.
[0082] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity, and for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode current collector can usually have a thickness of 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector can be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0083] As the negative electrode active material, a compound capable of reversible intercalation and deintercalation of lithium can be used. Specific examples include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; metal oxides capable of doping and undoping lithium such as SiOv (0 < v < 2), SnO2, vanadium oxides, and lithium vanadium oxides; or composites containing the metallic compound and the carbonaceous material such as Si-C composites or Sn-C composites. Any one or a mixture of two or more of these can be used. Further, a thin film of metallic lithium may be used as the negative electrode active material. Also, both low-crystalline carbon and highly crystalline carbon can be used as the carbon material. Representative examples of low-crystalline carbon include soft carbon and hard carbon, and representative examples of highly crystalline carbon include amorphous, plate-like, flaky, spherical, or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature calcined carbon such as petroleum or coal tar pitch derived cokes.
[0084] Also, the binder and the conductive material may be the same as those described for the positive electrode.
[0085] Meanwhile, in the secondary battery, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used as a separator in a secondary battery can be used without any particular limitation. In particular, it is preferable that the separator has low resistance to ion movement of the electrolyte and excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof can be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. can be used. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymeric substance can be used, and it can be selectively used in a single layer or multilayer structure.
[0086] On the other hand, the electrolyte may be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, or the like that can be used in the manufacture of a secondary battery, but is not limited thereto.
[0087] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0088] The organic solvent may be any solvent that can act as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that can be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as Ra-CN (Ra is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant, which can improve the charge / discharge performance of a battery, and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the performance of the electrolyte may be excellent if the cyclic carbonate and the chain carbonate are mixed at a volume ratio of about 1:1 to 1:9.
[0089] The lithium salt can be used without any particular limitation as long as it is a compound capable of providing lithium ions used in lithium secondary batteries. Specifically, the lithium salt can be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O2)2. The concentration of the lithium salt is preferably within the range of 0.1M to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that it can exhibit excellent electrolyte performance and lithium ions can move effectively.
[0090] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, or pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1% by weight to 5% by weight based on the total weight of the electrolyte.
[0091] As described above, the lithium secondary battery including the positive electrode active material according to the present invention has excellent capacity characteristics and high temperature stability, and can be usefully applied to portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).
[0092] In addition, the secondary battery according to the present invention can be used as a unit cell of a battery module, and the battery module can be applied to a battery pack. The battery module or the battery pack can be used as a power source for one or more medium- to large-sized devices, such as a power tool, an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV), or a power storage system.
[0093] Below, preferred examples are presented to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical spirit of the present invention. Naturally, such changes and modifications also fall within the scope of the appended claims.
[0094] Working Example Manufacture of positive electrode active material [Example 1] (1) Production of liquid intermediates - A step of leaching out the metal components in the raw material using an acid, removing impurities, and isolating the liquid phase intermediate. Laterite ore was pressure leached with sulfuric acid in an autoclave (HPAL (High Pressure Acid Leaching) method). The temperature was 250°C and the pressure was 4.46MPa. 350kg / ton of sulfuric acid was added based on the dry ore. The residue was then separated by settling, and the residual acid in the leachate was neutralized. The above process was repeated five times. The reaction at this time is as shown in the following reaction formula.
[0095] Ni(Co)O(s)+H2SO4(aq)=Ni(Co)SO4(aq)+H2O(1) 2FeOOH+3H2SO4=Fe2(SO4)3+4H2O Fe2(SO4)3+3H2O=Fe2O3+3H2SO4 MgO+H2SO4=MgSO4+H2O 3Al(OH)3+2H2SO4=H2OAl3(SO4)2(OH)6+2H2O
[0096] As described above, the liquid phase intermediate obtained after leaching the metal components using acid and removing the impurities contained 10.3 mol % nickel sulfate, 0.9 mol % cobalt sulfate, and 1.7 mol % manganese sulfate (cobalt / nickel content ratio=0.087), and the specific composition of the liquid phase intermediate was as shown in Table 1 below.
[0097] It is expressed based on 100% total weight, with the remainder consisting of other unavoidable impurities.
[0098] [Table 1]
[0099] (2) Co-precipitating a positive electrode active material precursor To 1 ton of the liquid phase intermediate obtained above, 316 kg of nickel sulfate and 77 kg of cobalt sulfate were further added.
[0100] Then, as described above, the liquid phase intermediate further charged with nickel sulfate, cobalt sulfate and manganese sulfate was adjusted to pH 11.0 by adding sodium hydroxide (NaOH) solution, and then charged at 0.32 L / hr into a 5L reactor initialized with nitrogen gas at 1 L / min, reactor temperature at 40 ° C, and stirring speed at 1000 RPM. Then, a 6M concentration ammonia solution (NH4OH, chelating agent) was continuously charged into the reactor at 0.032 L / hr, and 3M concentration sodium hydroxide (NaOH, hydroxide precipitant) was further charged to adjust the pH to 11, and the average residence time of the solution was 6 hours, and nickel-cobalt-manganese composite hydroxide was continuously obtained. The nickel-cobalt-manganese composite hydroxide thus obtained was filtered and then dried at 130 ° C for 24 hours to be used as a precursor before heat treatment.
[0101] The precursor and lithium hydroxide (LiOH.H2O) were placed in a high density polyethylene (HDPE) bottle in a molar ratio of 1:1.4, and zirconia balls were added so that the ratio of zirconia balls to raw materials was 5:1. The raw materials were then mixed in a solid state at 100 rpm through a ball mirror for 10 hours. The raw materials thus mixed in a solid state were separated from the zirconia balls, placed in a heating furnace, heated to 750°C at a rate of 1.25°C / min, and fired at 750°C for 10 hours in an oxygen atmosphere to produce a lithium composite metal oxide. The lithium composite metal oxide was LiNi 0.8 Co 0.1 Mn 0.1 The lithium composite metal oxide and ethanol thus prepared were placed in a 1L reactor in a weight ratio of 1:10, and the impeller was rotated at 1000 rpm for 1 hour to remove residual lithium, which was then vacuum filtered and vacuum dried at 130°C for 10 hours to produce a positive electrode active material.
[0102] The content of nickel element relative to the total amount of metals excluding lithium in the positive electrode active material was 80 at %.
[0103] [Comparative Example 1] Nickel, cobalt and manganese were smelted by a conventional method, and then nickel sulfate (NiSO4), cobalt sulfate (CoSO4) and manganese sulfate (MnSO4) were produced using the smelted nickel, cobalt and manganese sulfates. A metal solution was produced with the same molar ratios of nickel sulfate (NiSO4), cobalt sulfate (CoSO4) and manganese sulfate (MnSO4) as in the liquid phase intermediate of Example 1.
[0104] Specifically, the leachate obtained in step (1) was treated with an excess amount of hydrogen sulfide (HS) to obtain nickel sulfide (NiS), cobalt sulfide (CoS) and manganese sulfide (MnS). Nickel (Ni), cobalt (Co) and manganese (Mn) were extracted (reduced) from the nickel sulfide (NiS), cobalt sulfide (CoS) and manganese sulfide (MnS), and then re-sulfated to produce nickel sulfate (NiSO4), cobalt sulfate (CoSO4) and manganese sulfate (MnSO4). The molar ratios of these were then the same as those of the liquid phase intermediate in Example 1 to produce a metal solution.
[0105] Thereafter, a positive electrode active material was prepared using the metal solution in the same manner as in the step (2) of coprecipitating a positive electrode active material precursor.
[0106] The content of nickel element relative to the total amount of metals excluding lithium in the positive electrode active material was 80 at %, which was the same as in Example 1.
[0107] From the above results, it was found that the manufacturing method of the present invention, despite simplifying the smelting and liquefaction processes, exhibits effects equal to or greater than those of conventional manufacturing methods, and can reduce the time and cost required to manufacture positive electrode active material.
[0108] Any mere variations or modifications of the present invention belong to the scope of the present invention, and the specific scope of protection of the present invention will be made clear by the appended claims.
Claims
1. providing a feedstock containing nickel and cobalt; leaching metal components in the feedstock using an acid, removing impurities and isolating a liquid phase intermediate; introducing manganese sulfate into the separated liquid phase intermediate; and adding a chelating agent and a hydroxide precipitating agent to the separated liquid phase intermediate to co-precipitate a positive electrode active material precursor; The method for producing a high nickel positive electrode active material, wherein the step of leaching the metal components in the raw material using the acid is performed using a High Pressure Acid Leaching (HPAL) method.
2. 2. The method for producing a high-nickel positive electrode active material according to claim 1, wherein the raw material containing nickel and cobalt is nickel oxide ore or nickel sulfide ore.
3. 2. The method of claim 1, wherein the liquid phase intermediate comprises nickel sulfate, cobalt sulfate, and manganese sulfate.
4. The liquid phase intermediate contains nickel in an amount of 35% by weight to 65% by weight and cobalt in an amount of 1.5% by weight to 7% by weight. The method for producing a high-nickel positive electrode active material according to claim 1, wherein the liquid phase intermediate contains nickel in an amount of 35% by weight to 65% by weight and cobalt in an amount of 1.5% by weight to 7% by weight.
5. 2. The method for producing a high-nickel positive electrode active material according to claim 1, wherein the cobalt / nickel content ratio in the liquid phase intermediate is 0.03 to 0.
13.
6. 2. The method of claim 1, further comprising adding at least one selected from the group consisting of nickel sulfate and cobalt sulfate after the step of separating the liquid phase intermediate.
7. 2. The method of claim 1, further comprising the step of mixing the positive active material precursor with a lithium source material and calcining the mixture to prepare a lithium composite metal oxide.
8. The method for producing a high nickel positive electrode active material according to claim 7, wherein the lithium composite metal oxide is represented by the following Chemical Formula 1: [Chemical formula 1] Li a Ni b Co c Mn d M e O 2 In the formula 1, M is at least one selected from the group consisting of W, Cu, Fe, Ba, V, Cr, Ti, Zr, Zn, In, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and 0.9≦a≦1.5, 0.7≦b<1.0, 0<c<0.2, 0<d<0.2, and 0≦e≦0.
02.
9. 2. The method of claim 1, wherein the step of leaching the metal components in the raw material with the acid comprises leaching the raw material in sulfuric acid under high temperature and pressure using an autoclave.
10. 2. The method for producing a high-nickel positive electrode active material according to claim 1, wherein the positive electrode active material has a nickel content of 60 at % or more based on the total amount of metals excluding lithium.
11. The method for producing a high-nickel positive electrode active material according to claim 1, which does not include a step of reducing the liquid phase intermediate.
Citation Information
Patent Citations
Method for directly preparing nickel-cobalt-aluminum ternary cathode material precursor by using acid leaching solution of laterite nickel ore
CN107579218A
Method for producing ferronickel smelting raw material from low grade lateritic nickel ore
JP2012031446A
Method of preparing positive active material precursor
KR1020150075200A
Method for manufacturing cathode electrode materials
KR1020160063982A
Method for preparing ternary cathode material from laterite nickel ore nitric acid leaching solution
WO2020019920A1